Flexible electrochemical biosensors based on graphene nanowalls for the real-time measurement of lactate. (10th July 2017) - Chen, Qianwei; Sun, Tai; Song, Xuefen; Ran, Qincui; Yu, Chongsheng; Yang, Jun; Feng, Hua; Yu, Leyong; Wei, Dapeng
Abstract: We demonstrate a flexible biosensor for lactate detection based onl -lactate oxidase immobilized by chitosan film cross-linked with glutaraldehyde on the surface of a graphene nanowall (GNW) electrode. The oxygen-plasma technique was developed to enhance the wettability of the GNWs, and the strength of the sensor's oxidation response depended on the concentration of lactate. First, in order to eliminate interference from other substances, biosensors were primarily tested in deionized water and displayed good electrochemical reversibility at different scan rates (20–100 mV s −1 ), a large index range (1.0 μ M to 10.0 mM) and a low detection limit (1.0 μ M) for lactate. Next, these sensors were further examined in phosphate buffer solution (to mimick human body fluids), and still exhibited high sensitivity, stability and flexibility. These results show that the GNW-based lactate biosensors possess important potential for application in clinical analysis, sports medicine and the food industry.